155k views
0 votes
Hi, could I have some help answering this question in the picture attached?simplify the question

Hi, could I have some help answering this question in the picture attached?simplify-example-1

1 Answer

3 votes

\text{-42}s^(-1)t^{(2)/(3)}

Step-by-step explanation:


\begin{gathered} (7s^{(7)/(4)}t^{(-5)/(3)})(-6s^{(-11)/(4)}t^{(7)/(3)}) \\ =\text{ }(7s^{(7)/(4)}* t^{(-5)/(3)})(-6s^{(-11)/(4)}* t^{(7)/(3)}) \end{gathered}

Expand and collect like terms:


\begin{gathered} =\text{ }7s^{(7)/(4)}* t^{(-5)/(3)}*-6s^{(-11)/(4)}* t^{(7)/(3)} \\ =\text{ }7* s^{(7)/(4)}*-6* s^{(-11)/(4)}* t^{(-5)/(3)}* t^{(7)/(3)} \\ =\text{ 7 }*-6\text{ }*\text{ }s^{(7)/(4)}* s^{(-11)/(4)}* t^{(-5)/(3)}* t^{(7)/(3)} \\ =\text{ -42}*\text{ }s^{(7)/(4)}* s^{(-11)/(4)}* t^{(-5)/(3)}* t^{(7)/(3)} \end{gathered}

Bring the exponents having same base together:


\begin{gathered} \text{The multiplication betwe}en\text{ same base becomes addition } \\ \text{when the exponents are brought together} \\ =-42\text{ }*\text{ }s^{(7)/(4)-(11)/(4)}* t^{(-5)/(3)+(7)/(3)} \\ =\text{ -42 }* s^{(7-11)/(4)}* t^{(-5+7)/(3)} \\ =\text{ -42 }* s^{(-4)/(4)}* t^{(2)/(3)} \end{gathered}
\begin{gathered} =\text{ -42 }* s^{(-4)/(4)}* t^{(2)/(3)} \\ =\text{ -42 }* s^(-1)* t^{(2)/(3)} \\ =\text{ -42}s^(-1)t^{(2)/(3)} \end{gathered}

User Jorge Quintana
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.